2017
DOI: 10.1016/j.lfs.2017.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Swim training attenuates the adverse remodeling of LV structural and mechanical properties in the early compensated phase of hypertension

Abstract: Six weeks of swim training attenuates the adverse remodeling of LV structural and mechanical properties in the early compensated phase of hypertension in male SHR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
17
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 38 publications
6
17
1
3
Order By: Relevance
“…It is therefore possible that a high‐intensity exercise programme produces deleterious cardiac effects when performed under increased afterload. In fact, low‐intensity swimming improved adverse remodelling and myocyte contractility in young SHR . We also observed that light treadmill exercise over four months reduced myocardial fibrosis and attenuated ventricular dysfunction in ageing SHR .…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…It is therefore possible that a high‐intensity exercise programme produces deleterious cardiac effects when performed under increased afterload. In fact, low‐intensity swimming improved adverse remodelling and myocyte contractility in young SHR . We also observed that light treadmill exercise over four months reduced myocardial fibrosis and attenuated ventricular dysfunction in ageing SHR .…”
Section: Introductionsupporting
confidence: 61%
“…When subjected to voluntary wheel running, SHR had increased mortality and myocardial fibrosis with impaired LV dilatation, hypertrophy, and diastolic dysfunction . On the other hand, young and old SHR subjected to low‐intensity exercise showed improved cardiac remodelling and contractility with reduced fibrosis. Our study shows for the first time that light exercise is safe, reduces LA size, LV posterior wall thickness, and concentric cardiac remodelling, and improves functional capacity, diastolic function, and metalloproteinase‐2 levels in adult SHR.…”
Section: Discussionmentioning
confidence: 99%
“…Forty-eight hours after the last exercise session, isolation of LV myocytes was performed as described by Locatelli et al 15 Briefly, the animals were weighed and euthanized by cervical dislocation. The heart was excised, weighed, cannulated and perfused in the Langendorff's mode with the isolation solution of the following composition (in mM): 130 Na+, 5.4 K+, 1.4 Mg+, 140 Cl−, 0.75 Ca 2+ , 5.0 Hepes, 10 glucose, 20 taurine and 10 creatine, pH 7.3, at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…15 Briefly, myocytes were placed in a chamber with a glass coverslip base and bathed with a buffer solution containing (mM) 136.9 NaCl; 5.4 KCl; 0.37 NaH2PO4; 0.57 MgCl2; 5.0 Hepes = 5; 5.6 glucose and 1.8 CaCl 2 (pH = 7.4 at room temperature). Cells were visualized on a monitor with a camera (Myocam, Ionoptix, at 240 Hz) attached to a microscope using an image detector system (Ionwizard, Ionoptix).…”
Section: Methodsmentioning
confidence: 99%
“…Quando se pratica o esporte de modalidade aquática, os músculos estriados esqueléticos são requisitados mais que o normal, para suportar a sobrecarga que produz aumento na força muscular (Heywood et al, 2017), e quando o músculo se contrai perante alguma resistência, ocorre estímulo da síntese proteica formando fissuras nas fibras musculares (Takagi et al, 2017;Camera et al, 2017). Após a recuperação do exercício físico, novas proteínas são produzidas, as fibras musculares são recuperadas, tornando-se mais densas e hipertróficas (Palstra et al, 2014;Locatelli et al, 2017). Isto não foi observado na musculatura mastigatória do GE e GD quando comparados aos indivíduos sedentários saudáveis.…”
Section: Discussionunclassified